Overview on reactions with multi-enzyme systems - Findrik Blažević, Zvjezdana (Array, 2009)
Summary: Production of special chemicals and pharmaceuticals includes multi-step procedures that are still carried out in the traditional way: by isolating the intermediary product of each step and using it as a substrate for the next step, which is money and time consuming. These are also procedures that require many chemicals, energy and labour. Over the last couple of decades scientists have been working on new, integrated processes that require fewer resources and are more close to nature, as they produce less waste. These kinds of processes are discussed in this paper. The advantages of enzyme catalyzed reactions are well documented and numerous. Enzyme reactions are carried out at mild reaction conditions. The enzymes are enantioselective and stereoselective, which is important particularly for the pharmaceutical industry. By combining the action of different enzymes we can imitate the processes in the living cells and produce the desired compounds. Enzyme catalyzed reactions can also be combined with chemical reactions in one-pot chemo-enzymatic synthesis. The progress in the development of these reactions will be presented